An empirical note on entrepreneurship and unemployment: Further evidence from U.S. States. Issue 1 (11th April 2016) - Apergis, Nicholas; Payne, James E
Abstract : Purpose: – The purpose of this paper is to extend the existing literature on the causal dynamics between entrepreneurship and the unemployment rate (UR) in the use of the Kauffman Foundation index of entrepreneurial activity. Design/methodology/approach: – Recently developed panel unit root tests with recognition of cross-sectional dependence and panel cointegration/error correction modeling techniques are applied to US States. Findings: – The results indicate that the rate of entrepreneurship, the UR, and real per capita personal income are cointegrated. The panel error correction model reveals that bidirectional causality exists among the variables in both the short run and long run. With respect to entrepreneurship, an increase in the UR increases the rate of entrepreneurship, in turn, an increase in the rate of entrepreneurship lowers the UR. Moreover, the results also show a positive bidirectional relationship between the rate of entrepreneurship and real per capita personal income. Originality/value: – Unlike other standard measures of entrepreneurship, this is the first empirical study of the causal dynamics between entrepreneurship and the UR using the Kauffman Foundation index of entrepreneurial activity.